2021
DOI: 10.1109/access.2021.3067937
|View full text |Cite
|
Sign up to set email alerts
|

Double Slip Effects and Heat Transfer Characteristics for Channel Transport of Engine Oil With Titanium and Aluminum Alloy Nanoparticles: A Fractional Study

Abstract: The core purpose of this study is the formulation of a fractional model to anticipate the improvement in heat transfer potential of a particular diathermal oil i.e. engine oil under thermal radiative flux. The magnetohydrodynamic (MHD) freely convectional transport of two different types of engine oil based nanofluids comprised of Titanium (Ti 6 Al 4 V) and Aluminum (AA7075) alloy nanoparticles is considered in a vertical channel frame. In addition, the channel is assumed to be embedded in a permeable media an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Related studies are in References. [59][60][61][62][63] Therefore, it is perceived that a substantial number of studies have been completed to show the hydrothermal pattern of nanofluids or simple Newtonian liquid flow within a square chamber with bottom and top surfaces that are differentially heated. However, no such corresponding report or investigation is available for magnetized radiative ferrofluid flow when the lowermost and sidewall of the square chamber are both uniformly or nonuniformly heated, despite having several real applications as declared earlier.…”
Section: Introductionmentioning
confidence: 99%
“…Related studies are in References. [59][60][61][62][63] Therefore, it is perceived that a substantial number of studies have been completed to show the hydrothermal pattern of nanofluids or simple Newtonian liquid flow within a square chamber with bottom and top surfaces that are differentially heated. However, no such corresponding report or investigation is available for magnetized radiative ferrofluid flow when the lowermost and sidewall of the square chamber are both uniformly or nonuniformly heated, despite having several real applications as declared earlier.…”
Section: Introductionmentioning
confidence: 99%
“…Anwar et al 26 looked at a Brinkman‐type ferrofluid in similar work. The heat transfer performance of an engine oil‐based nanofluid flowing through a vertical channel was investigated by Asifa et al 27 Titanium nanoparticles have been shown to be more effective than aluminum alloy nanoparticles in improving engine oil heat transfer. Other related studies, such as in References [28, 29] can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%